KERUKUNAN ANTAR UMAT BERAGAMA (Studi Hubungan Antar Umat Beragama: Islam, Katolik, Kristen Protestan, dan Buddha di RW 02 Kampung Miliran, Kelurahan Muja-muju, Kecamatan Umbulharjo, Yogyakarta) - Syarifah, Nur (UIN Sunan Kalijaga Yogyakarta, 2013)
Religious plurality is a reality that cannot be denied or even elimi- nated. This fact leads to a logical consequence of the religious life, namely to coexist in the diversity of beliefs. This has happened in RW 02, Kampung Miliran, Yog yakarta. The people in this place live peacefully and in harmony with one another despite their different in religious affiliation. Departing from this reality, two questions arise: what is the basis of inter-religious har mony in RW 02, Kampung Miliran, and how this religious harmony is maintained in such a plu- ral society. The data for this study is collected by means of observa- tion, interview, and documentation. The materials are then analyzed using structural-functional theory of Talcott Parsons known with the ter m AGIL: Adaptation, Goal Attainment, Integration, and Latent Pat- ter n Maintenance.The study suggests that religion plays a pivotal role as it teaches foun- dation of mutual love and respect between religious communities. Hence the prevailing norms in Javanese society such as ethics, the principle of harmonious and respectful may be upheld. This research also portrays the application of religious teachings and the basic rules of society in everyday life. The application may be viewed in the people practice of Agustusan and Syawalan together (adaptation) as well as their subservience to the leaders of different religions in or- der to achieve a common goal (goal Attainment). With the assimilation of one another, the public then can minimize conflicts between faiths (integration). Although they disperse in such a melting pot, each still maintain (latent pattern maintenance) their religious principles and cul- tural nor ms.